The orchard house - Chiavaroli, Heidi (Tyndale House Publishers, 2020)
"Award-winning author Heidi Chiavaroli transports readers across time and place in this time-slip novel that will appeal to fans of Little Women. Two women, one living in present day Massachusetts and another in Louisa May Alcott's Orchard House soon after the Civil War, overcome their own personal demons and search for a place to belong. 2001 Abandoned by her own family, Taylor is determined not to mess up her chance at joining the home of her best friend, Victoria Bennett. But despite attending summer camp at Louisa May Alcott's historic Orchard House with Victoria and sharing dreams of becoming famous authors, Taylor struggles to fit in. As she enters college and begins dating, it feels like Taylor is finally finding her place and some stability . . . until Victoria's betrayal changes everything. 1865 While Louisa May Alcott is off traveling the world, Johanna Suhre accepts a job tending Louisa's aging parents and their home in Concord. Soon after arriving at Orchard House, Johanna meets Nathan Bancroft and, ignoring Louisa's words of caution, falls in love and accepts Nathan's proposal. But before long, Johanna experiences her husband's dark side, and she can't hide the bruises that appear. 2019. After receiving news of Lorraine Bennett's cancer diagnosis, Taylor knows she must return home to see her adoptive mother again. Now a successful author, Taylor is determined to spend little time in Concord. Yet she becomes drawn into the story of a woman who lived there centuries before. And through her story, Taylor may just find forgiveness and a place to belong." -- ONIX annotation.